(untitled) (Fiep Bulletin - online, 2013)
We observed a policy of encouraging physical activity, note that sedentary lifestyle has affected various social levels and age groups. The setting seems more negative than in women, the elderly and people with lower education. Thus, this study aims to estimate the prevalence of health problems among physically active women above fifty years in two sports institutions in Botucatu, São Paulo. We used a cross-sectional study subsidized by questionnaires. Among the results, we highlight older women in N2 (p <0.001). Approximately 8% reported heart problems, 56.2% and 52.1% osteoarticular problems hypertension. From the data presented, it was observed similarly to the literature. Also noteworthy is the complexity of variables involved in determining active lifestyle and understanding the relationship physical activity and active lifestyle. It is suggested studies considering other variables related to the epidemiological profile of this population, such as income, education, use of medications and types of physical activities. Still indicates the expansion of knowledge about conditions and lifestyle that could support new ways of meeting the needs of women over fifty, encouraging greater physical activity oriented and their contributions to the health scenario in the later years of life.